A light-triggerable nanoparticle library for the controlled release of non-coding RNAs - Josephine, Blersch (2019)
RNA-based therapies offer a wide range of therapeutic interventions including for the treatment of skin diseases; however, the strategies to deliver efficiently these biomolecules are still limited due to obstacles related to the cellular uptake and cytoplasmic delivery. Herein, we synthesized a triggerable polymeric nanoparticle (NP) library composed by 160 formulations, presenting physico-chemical diversity and differential responsiveness to light. Six formulations were more efficient (up to 500%) than commercial Lipofectamine in gene knockdown activity. These formulations had differential internalization by skin cells and the endosomal escape was rapid (minutes range) as shown by the recruitment of galectin-8. The NPs were effective in the release of siRNA and miRNA. Acute skin wounds treated with the top hit NP complexed with miRNA-150-5p healed faster than wounds treated with scramble miRNA. Light-activatable NPs offer a new strategy to deliver topically non-coding RNAs.